Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0127-001 24th March, 1937. Mr. E.E. Flemming, 16, Balmoral Gardens, EALING. W.13. Dear Mr. Flemming, Thank you very much for the cutting from the local newspaper, and I am sending the enclosed reply to the paper, which I hope will be published. Yours sincerely, Copy letter. 292C/946/2/127